2015
DOI: 10.1038/srep11066
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-protein ligase E3C promotes glioma progression by mediating the ubiquitination and degrading of Annexin A7

Abstract: The ubiquitin-protein ligase E3C (UBE3C) belongs to the E3 ligase enzyme family and implicates in the ubiquitin-proteasome pathway, thus regulates physiological and cancer-related processes. Here, we investigated the expression and roles of UBE3C in glioma. We demonstrated that UBE3C was overexpressed in glioma tissues and cell lines. Inhibition of UBE3C expression in glioma cells significantly decreased cell migration and invasion in vitro. Mechanistically, we disclosed that UBE3C physically interacted with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…The UBE3C ubiquitin ligase is involved in myriad cellular processes, such as proteasome processivity, interferon signaling, and cancer metastasis [11,12]. In summary (Figure 8), we solved the crystal structure of WT UBE3C HECT domain (aa 693-1083) at 2.7 Å and showed that the N-terminal extended region (aa 693-743)…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The UBE3C ubiquitin ligase is involved in myriad cellular processes, such as proteasome processivity, interferon signaling, and cancer metastasis [11,12]. In summary (Figure 8), we solved the crystal structure of WT UBE3C HECT domain (aa 693-1083) at 2.7 Å and showed that the N-terminal extended region (aa 693-743)…”
Section: Discussionmentioning
confidence: 92%
“…UBE3C (aa 1-1083), also known as RTA-associated ubiquitin ligase (RAUL), is a member of the 'other' subfamily of HECT E3 ligases. It contains an 'IQ' motif (aa 45-74) at its N-terminus and a HECT domain (aa 744-1083) at its C-terminus, which regulates several crucial cellular processes [11,12]. The HECT domain of UBE3C displays ∼30% sequence identity with the HECT domains of NEDD4 subfamily members, and ∼32% sequence identity with the HECT domains of the 'other' subfamily members.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, ANXA7 is a tumor suppressor protein. The expression of this protein is decreased in glioma tissues, and its degradation may contribute to glioma progression [18]. Moreover, loss of ANXA7 is associated with prognosis in glioblastoma patients, and ANXA7 is a strong predictor of patient outcome [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…ANXA7 is a tumor suppressor gene. ANXA7 protein expression decreased in glioma tissues, and ANXA7 degradation might contribute to glioma progression [21]. Furthermore, loss of ANXA7 is associated with glioblastoma patient prognosis, and its expression was a strong predictor of patient outcome [22,23].…”
Section: Discussionmentioning
confidence: 99%